Kesehatan Spiritual dan Kesiapan Lansia dalam Menghadapi Kematian - Ananda Ruth Naftali; Yulius Yusak Ranimpi; M. Aziz Anwar (Faculty of Psychology Universitas Gadjah Mada, 2017)
Spirituality is a harmonious relationship between man, nature, and God. Spirituality has dimensions that provide power when facing emotional stress, physical illness and death and affects human life in every stage of its development, including the elderly. One of the issues often faced by the elderly is associated with their preparation in the face of death and one of the factors that affect is spirituality. The purpose of this research was to describe the spiritual health and readiness of the elderly to face of death, both the elderly who were in Panti Wredha Salib Putih Salatiga and the elderly who lived with her family in Getasan. This study used qualitative research methods with descriptive phenomenology approach and comparative study design. Participants in this study amounted to 6 participants, 3 participants who stay at home and 3 participants who stay at home with their family. The results showed that spiritual health is affected by the meaning of life, the concept of religion and divinity, social interaction, the concept of health and illness, well-being and spirituality, as well as readiness to face death.